Standardization of Kinetic Determination of Nitrite Based on Its Catalytic Effect on an Indicator Reaction - Prasad, Surendra; Halafihi, Tu'ikolongahau (Asian Journal of Chemistry, 2010)
A catalytic kinetic procedure for nitrite determination based on its catalytic effect on the oxidation of brilliant cresyl blue (BCB) by bromate ion in acidic media is standardized and proposed. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of BCB at its λmax 595nm. The calibration graph is linear from 1-80 ng.ml–1 of nitrite. The detection limit is 5.8 ng.ml–1 of nitrite. Nitrite in the range of 10–80 ng.mL–1 has been determined successfully where recoveries were 97.3 ∼ 103.7% with the relative standard deviation 0.1 ∼ 0.8%. The effect of many foreign ions upon determination of 70 ng.mL–1 of nitrite has been studied and shown that most common cations and anions do not interfere in the determination except Fe2+ which was masked. The procedure was successfully applied for the determination of nitrite in wastewater and seawater with satisfactory results. The typical feature of this procedure is that the determination could be carried at normal temperature of 25ºC with analysis time of 4 min.